Knowledge and attitude on postpartum depression and the predicting factors among urban poor women in Klang Valley, Malaysia - Mahmud, Aidalina; Zakaria, Nurul Izati (Zes Rokman Resources, 2024)
Introduction: Postpartum depression (PPD) can be prevented and detected early, hence avoiding dreadful consequences. However, poor knowledge and negative attitude often prevent most women from seeking early help and treatment. Objective: Our study aimed to determine the knowledge and attitude levels on PPD, and the associated factors among urban poor women. METHODOLOGY: A cross-sectional study was conducted in April to May 2024 among women aged 18 years and above living in the People’s Housing Program (PPR) in Klang Valley. A two-stage random sampling method was used to sample 312 women from 13 selected PPRs. A self-administered questionnaire adapted from previous studies was used, covering sociodemographic and socioeconomic factors, mental health history, exposure to mental health information, knowledge, and attitude on PPD. Results: A total of 281 respondents participated (response rate 90%). More than half of participants demonstrated good knowledge (59.8%) and positive attitude (53.4%) towards PPD. Multiple logistic regression analyses showed that women with at least one child (aOR: 1.974, 95% CI: 1.02-3.538) were associated with good knowledge about PPD. Additionally, employed women (aOR: 3.665, 95% CI: 2.122- 6.329), women with higher education (aOR: 3.278, 95% CI: 1.533-7.893) and married women (aOR: 2.419, 95% CI 1.416-4.134) were associated with positive attitude towards PPD. Conclusion: In this study, slightly more than half of the respondents had good knowledge and attitude on PPD. Women with at least one child have good knowledge, while women who are working, more educated and married had better attitude. Although the proportion of women with good knowledge and attitude on PPD is moderate, educational, and supportive interventions are still needed. Findings of this study highlight the importance of targeted educational and fostering positive attitudes support interventions that consider parity, employment status, education level, and marital status, through community-based programs and policy initiatives.